Pengembangan Media Audio Visual Menggunakan Contextual Teaching and Learning (CTL) dalam Pembelajaran Menulis Paragraf Narasi pada Siswa Kelas VII SMP - M. Bahri Arifin; Yulinda Ari Wardani (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this study was to develop an audio-visual media design in learning to write narrative text using the Contextual Teaching and Learning model and to determine the feasibility of audio-visual media designed for learning in junior high schools. This development is expected to help teachers in the learning process and attract students to participate in learning to write narrative paragraphs actively. This development research uses a qualitative approach with a development model, according to Alessi and Trollip (2001). Initial data were obtained for needs analysis before developing instructional media. Meanwhile, the data validated by design experts, linguists, and material experts are used to determine the feasibility of the media that has been developed. The data collection was done by using a questionnaire method. Development is carried out in three stages, namely planning, design, and development. The results of the due diligence of the three experts are as follows. The results of the media expert's feasibility test got a score of 40 with a percentage of 90.91%, so it was categorized as very feasible. The linguist gave a feasibility test score of 22 with a percentage of 91.67% and was categorized as very feasible. The feasibility test of the material expert scored 42 with a percentage of 87.5% and was categorized as very feasible. Based on these results, it can be concluded that the developed audio-visual media has met the very feasible criteria.